Efficacy and Bleeding Risk of Antithrombin Supplementation in Patients With Septic Disseminated Intravascular Coagulation: A Third Survey. (July 2017) - Iba, Toshiaki; Gando, Satoshi; Saitoh, Daizoh; Ikeda, Toshiaki; Anan, Hideaki; Oda, Shigeto; Kitamura, Nobuya; Mori, Shigeru; Kotani, Joji; Kuroda, Yasuhiro
Introduction: Although recent studies have reported the efficacy of antithrombin (AT) supplementation for sepsis-associated disseminated intravascular coagulation (DIC), the factors that influence AT's effect have not been sufficiently studied. The purpose of this survey was to identify factors that modulate the effects and the adverse effects of AT. Methods: We performed a multi-institutional survey. The data from 159 patients with septic DIC with AT ≤70% and who had undergone AT supplementation were analyzed. The patients' demographic characteristics, including the infection site, baseline sepsis-related organ failure assessment (SOFA) score, baseline DIC score, and baseline AT activity, were analyzed in relation to the 28-day mortality. Bleeding-related adverse events were also examined. Results: Overall, 116 patients survived and 43 did not (28-day mortality: 27.0%). A logistic regression analysis revealed that the baseline SOFA score (odds ratio [OR]: 0.816, P = .001), coadministration of recombinant thrombomodulin (rTM; OR: 3.989, P = .006), and respiratory tract infection (OR: 0.129, P = .000) were significantly associated with the survival. Survivors exhibited a higher peak AT activity than nonsurvivors (85.1% vs 65.0%, P = .027). Bleeding events were observed in 4.13% (major bleeding: 1.65%) of the patients, and the coadministration of rTM did not increase the risk of bleeding (with rTM: 4.11% vs without rTM: 4.17%). Heparin was concomitantly used in 22 (18.2%) cases, and its use nonsignificantly increased the bleeding risk (with heparins: 9.09% vs without heparins: 3.03%; P = .224). Conclusion: The coadministration of rTM may improve survival without increasing the risk of bleeding in patients with sepsis-associated DIC treated with AT.